Direct investment in South East Asia by the NIEs: trends and prospects - LALL, S. (PSL Quarterly Review, 2013)
Newly industrialising economies (NIEs) in Asia are actively investing in other countries within the region. There are two types of foreign direct investments (FDI). One is characterised by high technology transfers and financing from large companies, the other by comparatively low technology transfers from small and medium scale groups. Of the NIEs, Korea is predicted to expand its FDI within the 1990s, while Hong Kong is expected to move its industry base away from the colony. Singapore and Taiwan are both foreseen to expand into more advanced investments. Other FDI trends and patterns are discussed. JEL: E22, F21